Induction of estrus and fertility using subcutaneous implants in anestrous dairy goats - Leonel Avendaño (Interciencia, 2003)
Forty-four multiparous dairy goats, purebreed and crossbreedof Nubian, Toggenburg, Saanen, La Mancha and FrenchAlpine breeds were used to determine the effect of Norgestomet(3 and 6mg) when used in conjunction with eCG during theanestrous season on the time to onset of estrus, induced estrous,fertility, gestation duration, number of kids per doe and kidsbirth weights. The animals were assigned randomly to 3 groups;a control group (n=15) without hormonal treatment, anothergroup (n=14) treated with 3mg of Norgestomet (half implant)placed subcutaneously in the ear for 11d; and a third group(n=15) treated with a 6mg Norgestomet implant placed in thesame location for 11d. Both treated groups received 500IU eCGi.m. 24h prior to progestagen removal. The group treated with6mg Norgestomet had a shorter (P<0.05) interval fromprogestagen removal to estrus than the group treated with 3mg(16.8 ±0.76h vs 24.6 ±0.8h). Nevertheless, the induced estrus(100 vs 93%) were similar (P>0.05) in both groups. Fertilitywas higher (P<0.10) in the 6mg group (87 vs 57%). No estrousactivity was observed in the control group. Gestation length,mean number of kids per doe and mean weight at birth werealso similar (P>0.05) in the 3 and 6mg groups. Dairy goats implantedwith 3mg Norgestomet exhibited similar estrous induction,but had lower fertility rate than the group implanted with6mg.